Considering the asymmetric effect of financial deepening on environmental quality in BRICS economies: Policy options for the green economy. (10th January 2022) - Li, Xiaolong; Ozturk, Ilhan; Majeed, Muhammad Tariq; Hafeez, Muhammad; Ullah, Sana
Abstract: This study aims to estimate the nexus between financial deepening and environmental quality in Brazil, Russia, India, China, and South Africa (BRICS) economies by using the data over 1990–2019. For analysis, we relied on panel linear and nonlinear autoregressive distributed lag (ARDL). Three different variables i.e. financial deepening index, financial institution deepening, and financial market deepening are used to represent financial deepening in BRICS countries. In the long run, our linear models confirmed the positive role of financial deepening in improving environmental quality. Conversely, the symmetric estimates of financial institution deepening and financial market deepening are positively significant implying that both these measures cause the CO2 emissions to rise, thus hurts the environmental quality in BRICS in long run. In the non-linear models, the positive shock in all the measures of financial deepening increases the CO2 emissions while the negative shock deteriorates the CO2 emissions, in all three models, in the long run. In the short-run, the variables of financial deepening provide mixed results during linear and non-linear analysis. Moreover, CO2 emissions respond asymmetrically to a positive and negative change in financial deepening in the long run only. Although financial deepening in the BRICS economies helps reduce the CO2 emissions, the BRICS are still among the top ten emitters of the world. Therefore, the role of financial deepening should be further enhanced in achieving a sustainable environment. Highlights: We examined the nexus between financial deepening and environmental quality in BRICS economies. In the non-linear models, the positive shock in all the measures of financial deepening increases the CO2 emissions, while the negative shock deteriorates the CO2 emissions in the long run. In the short-run, the variables of financial deepening provide mixed results during non-linear analysis. The role of financial deepening should be further enhanced in achieving a sustainable environment.